Social Media as a Platform for Collaborative Innovation: Enhancing Human Capital and Urban Sustainability in Tehran - Tajari Gharibabadi, Zabihollah; Radfar, Majid; Salari, Mahshid (Digital Transformation and Administration Innovation, 2025)
This study aims to explore how social media platforms contribute to collaborative innovation, the development of human and social capital, and the promotion of urban sustainability practices in Tehran. Employing a qualitative research design based on Grounded Theory, this study collected data through in-depth, semi-structured interviews with 12 purposefully selected participants actively engaged in social media-based knowledge sharing, environmental activism, and innovation. Participants were diverse in terms of age, gender, education, and profession. Data collection continued until theoretical saturation was achieved. Thematic analysis was conducted using open, axial, and selective coding procedures. Credibility of the findings was ensured through member checking and triangulation of viewpoints. Analysis revealed four main categories through which social media enhances urban innovation and sustainability: (1) enhancing environmental literacy through awareness campaigns; (2) enabling collaborative innovation via citizen problem-solving; (3) fostering behavioral change through peer-generated content; and (4) facilitating social mobilization through hashtag activism and online coordination. Participants emphasized the role of social platforms in generating ecological awareness, sharing grassroots solutions, and fostering digital communities that promote sustainable behaviors. The findings highlight the interplay between human capital and social capital as central to the innovation potential of social media in Tehran’s urban context. Social media functions as a participatory infrastructure for civic innovation and sustainability in Tehran, enabling decentralized learning, peer-to-peer influence, and digital coordination. These platforms empower citizens to share knowledge, co-create urban solutions, and engage in environmental advocacy, particularly in contexts where formal institutional pathways are limited. The integration of digital tools into urban governance and community development strategies is essential for fostering inclusive, sustainable urban futures.